IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH USING MEDIA PICTURE OF 2016/2017 SECOND GRADE OF SD RAUDHATUL HASANNAH - Adetia Pratiwi; Ayu Indari (STKIP Budidaya Binjai, 2022)
The present classroom action research dealt with the improving vocabulary through media picture to the second grade students of SD Raudhatul hasanah in academic year 2016/2017. The present classroom action investigation was basically triggered by the fact that the subjects under study still faced problem in learning vocabulary. The problem of the study could be formulated as follows: can vocabulary mastery of the second grade students of SD Raudhatul hasanah in academic year 2016/2017 be improved through picture? There is one class as many as thirty students in SD Raudhatul hasanah. In this classroom action study, the teaching and learning processes were divided into two cycles where each cycle consisted of two sessions. The obtained data of the present classroom action study were collected through the administration of pre-test, post-test, and questionnaire which were analyzed descriptively. The present classroom action study was started with administering pre-test to the subjects under study. The grand mean figure of post test scores obtained by the subjects under study in cycle I was 51,2 and in cycle II was 85,1. There was a significant difference of the grand mean figure between cycle I and cycle II. The difference of the grand mean figure of cycle I and cycle II was 33,9. These findings clearly showed that picture could improve vocabulary mastery of the second grade students of S D Raudhatul hasanah in academic years 2016/2017. The result of the data analysis of questionnaire score showed the comparative percentage figures of 71.61% for option A, 27.34% for option B, 1.05% for option C, and 0% for option D. The comparative percentage figures clearly showed the subjects’ attitude and motivation in learning vocabulary changed positively.